Microfoundations of dynamic coopetition capabilities in firms from a microbrewery cluster (REGE Revista de Gestão, 2023)
Purpose – The objective of this research was to analyze the microfoundations of dynamic capabilities used by microbreweries in Porto Alegre (Brazil) in their coopetition strategies. Design/methodology/approach – A case study with a qualitative approach was developed. Data were collected during interviews with owners of eleven microbreweries, via analysis of documents, and non-participatory observation. The authors used the content analysis technique to infer knowledge.Findings – We identified the microfoundations of dynamic coopetition capabilities including collective purchases, shared distribution expenses, shared production, education of consumers and other beer producers, group interaction, and a business roundtable with entrepreneurs from the food and drink sector in the hospitality industry.Research, Practical & Social implications – We developed a framework that considers the relationship between the microfoundations of dynamic capabilities and coopetition regarding the paradox between competition and cooperation. It is relevant to identify different actors’ movements and the potential outcomes of coopetitive strategies, which yield a competitive advantage for the cluster.Originality/value – Our study highlights how small companies can jointly develop competitive advantage in a market dominated by a large company.